»Missionsbudet«s tilblivelse - Hansen, Carl Rise (Kirkehistoriske Samlinger, 1991)
»Missionsbudet« was a missionary periodical published 1888-1907. The leading Danish missionary society Dansk Missionsselskab (DMS) published a periodical »Dansk Missionsblad«, which never gained a wide circulation. In the 1880’es the balance sheet of the society showed a deficit, and the Rev. C. Asschenfeldt-Hansen, well known in the history of the Indre Mission, wrote in 1887 to the chairman of the DMS and to the executive committee of the society proposing a new periodical at a lower price and with a more popular and devotional content. The executive committee approved the proposal, but wished in stead of the suggested co-editor, the Rev. Moe, who had used disparaging words about the Grundtvigian movement, the Rev. Th. L0gstrup, at that time member of the executive committee and later managing secretary of the DMS; he named the new periodical, but it was the energy and work of Asschenfeldt-Hansen, who marked the editing through 20 years of the new periodical. As early as 1889 the new paper had 21.000 subscribers (compared to the 2340 then of the »Dansk Missionsblad«). The new periodical nourished interest in many Danish homes for foreign missions, especially in the Indre Mission. The number of subscribers to the »Dansk Missionsblad« increased until in 1907 the two periodicals had almost the same number ofsubscribers. It is supposedly the break between the Rev. L0gstrup and the DMS that made an end to the »Missionsbudet«, but Asschenfeldt-Hansen went on with a new periodical »Det lille Missionsbud« (The little missionary messenger), edited for children.